A lithium supplement and preparation method thereof, and lithium ion battery
By filling the conductive network of carbon materials with lithium oxalate and transition metal catalysts, the problem of lithium oxalate supplementation agent with high decomposition voltage in low voltage systems is solved, achieving more efficient lithium ion release and battery performance improvement.
Patent Information
- Application Number
- CN202411216028.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-09-02
AI Technical Summary
Lithium oxalate supplementation agent has a high decomposition voltage in low-voltage systems, making it difficult to effectively use in low-voltage lithium iron phosphate systems. The commonly used catalysts are complex and costly.
By filling the conductive network built with carbon materials with lithium oxalate and catalyst, the catalyst uses transition metal acetate, transition metal oxalate, transition metal citrate and its hydrates to reduce the decomposition voltage of lithium oxalate.
It effectively reduces the decomposition voltage of lithium oxalate supplementation agent, improves the decomposition capacity, and realizes the more efficient release of lithium ions at lower voltages, improving the energy density and cycle life of the battery.
Smart Images

Figure CN118763221B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium supplement and a preparation method thereof, and a lithium ion battery. Background Art
[0002] In lithium-ion batteries, lithium supplements are a very promising additive for lithium-ion batteries. On the one hand, lithium supplements can make up for the loss of lithium ions during the initial charge and discharge, thereby increasing energy density; on the other hand, they can make up for the loss of lithium at the positive electrode during the cycle, thereby increasing cycle stability. Commonly used lithium supplements include lithium metal, lithium nickelate, lithium ironate, lithium oxalate, etc. Among them, lithium oxalate has attracted widespread attention due to its advantages such as stability in the air, non-absorption of water, and no residue after decomposition. However, the decomposition voltage of lithium oxalate is relatively high, which needs to be above 4.7V, which makes lithium oxalate unsuitable for low-voltage systems, especially low-voltage lithium iron phosphate systems.
[0003] At present, lithium oxalate is mostly physically mixed with carbon materials, catalysts, etc. by mechanical methods (such as ball milling and sand milling) to reduce the decomposition voltage of lithium oxalate and promote the decomposition of lithium oxalate. However, under this method, the poor combination effect between lithium oxalate, carbon materials, and catalysts makes it difficult to build a good conductive network between lithium oxalate, carbon materials, and catalysts to ensure good transmission of electrons and ions. On the other hand, common catalysts are mainly transition metal oxides, carbides, nitrides, phosphides, etc. The catalytic effect of such materials is general, and it is difficult to fully reduce the decomposition voltage of lithium oxalate, and it is necessary to prepare nano-scale materials to fully guarantee the catalytic effect, which is complicated to prepare and costly. Therefore, it is a technical problem to be solved in this field to select suitable catalysts and preparation methods to effectively reduce the decomposition voltage of lithium oxalate and maximize the capacity of lithium oxalate, and to make the preparation process simple, easy to operate, low-cost, and conducive to mass production. Summary of the invention
[0004] The present invention aims to solve the above problems by providing a lithium supplement and a preparation method thereof, and a lithium ion battery, thereby reducing the decomposition voltage of the lithium oxalate lithium supplement and increasing the decomposition capacity of the lithium oxalate lithium supplement.
[0005] To achieve the above-mentioned purpose, the present invention provides a lithium supplement, which includes lithium oxalate, a carbon material and a catalyst, wherein the lithium oxalate and the catalyst are filled in a conductive network constructed by the carbon material; wherein the catalyst includes at least one of transition metal acetate, transition metal oxalate, transition metal citrate and hydrates thereof.
[0006] The lithium supplement agent is composed of lithium oxalate, carbon material and catalyst. The lithium oxalate and the catalyst are jointly filled in a multidimensional conductive network constructed by the carbon material. This structure not only enhances the structural stability of the material, but also improves the transmission efficiency of electrons and ions. The catalyst is selected to include at least one of transition metal acetate, transition metal oxalate, transition metal citrate and its hydrate. These organic metal salts play a key role in the lithium supplement reaction of lithium oxalate. Because they have catalytic activity or the decomposition products under high voltage have catalytic activity, they catalyze the decomposition of lithium oxalate, thereby effectively reducing the decomposition voltage of lithium oxalate, so that lithium ions can be released more efficiently during the battery charging process. The lithium oxalate lithium supplement agent provided by the present invention has an average decomposition voltage of less than 4.25V and a decomposition capacity between 300mAh / g-500mAh / g.
[0007] Specifically, at high potential, transition metal ions of transition metal acetate, transition metal oxalate, and transition metal citrate are oxidized in situ to transition metal oxides or other substances, and other ions in the battery system move in a directional manner to balance these electrons and ions, so that acetate, oxalate, and citrate are decomposed into gases such as CO2 and CO and discharged. The in-situ generated transition metal oxides are finer and tightly combined with lithium oxalate and carbon materials, and have better catalytic activity, thereby promoting the decomposition of lithium oxalate.
[0008] Lithium oxalate, as a lithium salt, acts as a lithium source in the battery and releases lithium ions through electrochemical reactions. Carbon materials, such as graphite, carbon nanotubes or graphene, are the basis for building a conductive network. They have excellent electrical conductivity and mechanical properties, which can effectively support the distribution of lithium oxalate and catalysts, while promoting the rapid transmission of electrons and lithium ions. The catalyst accelerates the release of lithium ions by promoting the decomposition of lithium oxalate, thereby improving the reaction speed and efficiency of the battery.
[0009] In any of the above technical solutions, the transition metal in the catalyst includes at least one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, and W.
[0010] Adding transition metal acetates, transition metal oxalates, and transition metal citrates as catalysts to lithium supplements is mainly to utilize the electrochemical activity of these organic transition metal salts to promote the decomposition process of lithium oxalate. These metal catalysts can accelerate the release rate of lithium ions and effectively reduce the decomposition voltage of lithium oxalate during battery charging, thereby allowing the battery to complete the lithium supplement process at a lower voltage and improve the battery's energy density and cycle life.
[0011] In any of the above technical solutions, the mass ratio of lithium oxalate, carbon material and catalyst is (60-98):(1-39):(1-39).
[0012] Lithium oxalate is the main active material, with a high proportion of lithium oxalate, ensuring sufficient lithium ion supply to support the high energy demand of the battery. Carbon material is used as a conductive framework, with a lower proportion in the overall mixture, but sufficient to provide the necessary electronic conductivity and structural support. The content of the catalyst is also within a relatively low range, in order to ensure the decomposition efficiency of lithium oxalate while maximizing the content of lithium oxalate, thereby improving the release rate of lithium ions and the overall performance of the battery.
[0013] By adjusting the ratio of the three materials, the best performance balance can be found to achieve the highest electrochemical efficiency and the best battery performance. This range of adjustment allows the lithium supplement to be optimized according to different application requirements, such as increasing the proportion of lithium oxalate in applications that require higher energy density, or increasing the proportion of carbon materials when higher conductivity is required. By fine-tuning the ratio of ingredients, costs can be controlled while maintaining performance, making the production process more economical and efficient.
[0014] In any of the above technical solutions, the morphology of the lithium supplement agent includes at least one of secondary spherical particles composed of primary particles and secondary block particles composed of primary particles.
[0015] The lithium supplement in the form of secondary spherical or block particles is formed by the aggregation of multiple primary particles into larger spherical or block particles. This structure is beneficial to improving the uniformity and reaction area of the material while ensuring the overall stability of the material, preventing lithium oxalate from losing electrical contact with the carbon material and the catalyst during the slurry stage, thereby ensuring that its electrochemical activity in the battery system can be fully exerted.
[0016] In any of the above technical solutions, the particle size D50-1 of the primary particles is 20nm-200nm; and / or the particle size D50-2 of the secondary spherical particles is 3μm-30μm; and / or the particle size D50-3 of the secondary block particles is 3μm-30μm.
[0017] As the basic building block, primary particles within the particle size range of 20nm-200nm are conducive to maintaining high surface activity and faster reaction kinetics, accelerating the transmission of lithium ions, and promoting the decomposition of lithium oxalate at a lower voltage. By aggregating fine primary particles into larger spherical particles or block particles, the structural stability and ease of handling of the particles can be improved, preventing lithium oxalate from breaking during the homogenization stage while maintaining good electrochemical properties. This particle size range helps the lithium oxalate supplement to perform its lithium supplement performance in the battery system.
[0018] In any of the above technical solutions, the carbon material includes at least one of a zero-dimensional material, a one-dimensional material or a two-dimensional material.
[0019] Zero-dimensional materials refer to nanoparticles or quantum dots. These materials are extremely small in all three dimensions, so they have a high specific surface area, which significantly improves electrochemical activity and catalytic performance. One-dimensional materials such as carbon nanotubes or carbon nanofibers are known for their excellent electrical conductivity and mechanical properties. They are very suitable as electrode materials and can effectively improve the conductivity and structural strength of batteries. Two-dimensional materials such as graphene have a unique layered structure, provide extremely high surface area and excellent electronic and thermal conductivity, and are suitable for high-performance batteries and supercapacitors.
[0020] The use of these carbon materials of different dimensions can customize battery performance according to specific application requirements, such as enhancing the electrochemical reaction rate through zero-dimensional materials, or improving the structural stability and conductivity of the electrode through one-dimensional materials. Two-dimensional materials such as graphene can achieve high energy density and fast charge transfer in batteries, which plays an important role in improving the charging and discharging speed and power output of batteries. Combining these carbon materials of different dimensions can achieve complementary material properties, such as maintaining or enhancing the mechanical properties and thermal stability of the material while enhancing the electrochemical performance.
[0021] The present invention also provides a method for preparing a lithium supplement, which is used to prepare the lithium supplement as described above, and the preparation method comprises the following steps: S1, dissolving, stirring, and ultrasonically dispersing lithium oxalate, a carbon material, and a catalyst in sequence to obtain a slurry; S2, spray-drying and granulating the slurry in sequence to obtain a powder material; S3, drying the powder material to obtain a lithium supplement.
[0022] In the pretreatment mixing step, lithium oxalate, carbon material, and catalyst are dissolved, stirred, and ultrasonically dispersed in sequence, which helps ensure that all ingredients are evenly mixed to form a stable slurry. The prepared slurry is then quickly dried by spray drying technology and then granulated. This process not only removes the solvent in the slurry, but also converts it into a more uniform and suitable powder form through granulation. Finally, the powder material is finally dried to remove possible residual moisture and ensure that the final lithium supplement has good storage and use stability.
[0023] Furthermore, by dissolving lithium oxalate and the catalyst in water and then spray drying, the two substances can be uniformly precipitated together in the form of nanoparticles and composited with the carbon material. This method not only simplifies the production process, but also ensures the high uniformity and high performance of the composite material. During the charging process of the battery, this structure can maximize the lithium replenishment effect of lithium oxalate and improve the overall performance and life of the battery. Among them, the spray drying form includes rotary dispersion disk spray drying and jet two-fluid spray drying.
[0024] In any of the above technical solutions, the dissolution in step S1 specifically includes: dissolving lithium oxalate and the catalyst in water to obtain a mixed solution, and then adding the carbon material to the mixed solution; wherein the carbon material is in the form of at least one of powder or slurry.
[0025] In step S1, lithium oxalate and the catalyst are first dissolved in water to form a mixed solution. This operation ensures that the lithium oxalate and the catalyst can be fully dissolved, creating conditions for the subsequent mixing and reaction. Next, the carbon material is added to the mixed solution in the form of powder or slurry. The addition of the carbon material not only enhances the conductivity of the solution, but also provides better structural stability and battery performance. To ensure the dispersibility of the carbon material, the carbon material is used in the form of a dry powder material and a slurry. The slurry contains a dispersant to improve the dispersibility of the carbon material.
[0026] By pre-dissolving lithium oxalate and the catalyst in water before adding the carbon material, it is more effective to ensure that all ingredients are evenly mixed, which is critical to the quality and consistency of the final product. This dissolution and mixing method can speed up the production process, simplify the operation steps, and help improve the overall preparation efficiency.
[0027] In any of the above technical solutions, the concentration of lithium oxalate in the slurry is less than the saturation concentration of lithium oxalate.
[0028] The concentration of lithium oxalate used is set to be lower than its saturation concentration in the corresponding solvent. This means that the lithium oxalate is completely dissolved in the slurry, and there are no undissolved solid particles, thus ensuring the uniformity and stability of the solution. Keeping the concentration of lithium oxalate below the saturation point can prevent crystallization or precipitation during the preparation process or long-term storage, thereby improving the stability of the slurry; it can also ensure a more uniform distribution of materials, which is particularly important in the electrode coating process and helps to improve the consistency of battery assembly and the performance of the final battery; solutions that do not reach the saturation concentration have good fluidity and processability, and are easy to adjust and apply in subsequent processing steps, providing greater flexibility for battery design and manufacturing.
[0029] The present invention also provides a lithium ion battery, which includes the lithium supplement agent as described above.
[0030] After adopting the technical solution of the present invention, the following technical effects can be achieved:
[0031] (1) The lithium oxalate supplement catalyst provided by the present invention has a good catalytic effect, can significantly reduce the decomposition voltage of the lithium oxalate supplement, and promote the use of the capacity of the lithium oxalate supplement. The catalyst can be dissolved in water together with lithium oxalate to achieve uniform mixing in ionic state, and after spray drying, they are precipitated in situ to form uniformly mixed fine nanoparticles, and are compounded with carbon materials to form good contact, ensuring smooth transmission of ions and electrons to reduce the decomposition voltage;
[0032] (2) The carbon material provided by the present invention can construct a multi-dimensional conductive network. Especially when using flaky conductive carbon materials such as graphene, it can also prevent lithium oxalate and catalyst from losing electrical contact with graphene during the battery homogenization stage, resulting in an increase in decomposition voltage and deterioration of performance;
[0033] (3) The present invention prepares a lithium oxalate lithium supplement material with good performance by limiting the catalyst form, constructing a multi-dimensional conductive network and a specific preparation method. The lithium oxalate lithium supplement prepared in this form can decompose and release lithium elements to the maximum extent during the charging process, thereby maximizing the lithium supplement effect of the lithium oxalate particles. The lithium oxalate lithium supplement produced by this method has low cost, a simple preparation process, and is easy to operate, which is conducive to mass production and has practical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0035] Figure 1 This is a SEM image of a lithium supplement provided in Example 1 of the present invention;
[0036] Figure 2 This is a SEM image of a lithium supplement provided in Example 4 of the present invention;
[0037] Figure 3 This is a SEM image of a lithium supplement provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0038] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] An embodiment of the present invention provides a lithium supplement, which includes lithium oxalate, a carbon material and a catalyst, wherein the lithium oxalate and the catalyst are filled in a conductive network constructed by the carbon material; wherein the catalyst includes at least one of transition metal acetate, transition metal oxalate, transition metal citrate and hydrates thereof.
[0040] The lithium supplement agent is composed of lithium oxalate, carbon material and catalyst. The lithium oxalate and the catalyst are jointly filled in a multidimensional conductive network constructed by the carbon material. This structure not only enhances the structural stability of the material, but also improves the transmission efficiency of electrons and ions. The catalyst is selected to include at least one of transition metal acetate, transition metal oxalate, transition metal citrate and its hydrate. These organic metal salts play a key role in the lithium supplement reaction of lithium oxalate. Because they have catalytic activity or the decomposition products under high voltage have catalytic activity, they catalyze the decomposition of lithium oxalate, and then can effectively reduce the decomposition voltage of lithium oxalate, so that lithium ions can be released more efficiently during the battery charging process. The lithium oxalate lithium supplement agent provided in this embodiment has an average decomposition voltage of less than 4.25V and a decomposition capacity of between 300mAh / g-500mAh / g.
[0041] Among them, under high potential, the transition metal ions of transition metal acetate, transition metal oxalate and transition metal citrate are oxidized in situ to transition metal oxides or other substances, and the directional movement of other ions in the battery system balances these electrons and ions, so that acetate, oxalate and citrate are decomposed into gases such as CO2 and CO and discharged. The transition metal oxides generated in situ are finer and tightly combined with lithium oxalate and carbon materials, and have better catalytic activity, thereby promoting the decomposition of lithium oxalate.
[0042] Specifically, lithium oxalate, as a lithium salt, acts as a lithium source in the battery and releases lithium ions through electrochemical reactions. Carbon materials, as the basis for building a conductive network, such as graphite, carbon nanotubes or graphene, have excellent electrical conductivity and mechanical properties, which can effectively support the distribution of lithium oxalate and catalysts, while promoting the rapid transmission of electrons and lithium ions. The catalyst accelerates the release of lithium ions by promoting the decomposition of lithium oxalate, thereby improving the reaction speed and efficiency of the battery.
[0043] By limiting the structure and components of the lithium oxalate lithium supplement, a good combination is formed between lithium oxalate, carbon material and catalyst, which can fully reduce the decomposition voltage. The lithium oxalate lithium supplement is applied to the positive electrode material to maximize the lithium supplement effect of lithium oxalate. Among them, the catalyst has good catalytic effect and processability. The catalyst is used in the lithium oxalate lithium supplement, which can significantly reduce the decomposition voltage of the lithium oxalate lithium supplement and maximize the lithium supplement effect of lithium oxalate.
[0044] It should be noted that, by replacing lithium oxalate in the lithium supplement agent with sodium oxalate, a sodium oxalate sodium supplement agent can be obtained, which can be applied to sodium ion batteries or lithium sodium hybrid batteries to achieve the sodium supplement effect. The sodium supplement agent has the same beneficial effects as the lithium supplement agent provided in this embodiment.
[0045] In some embodiments of the present application, the transition metal in the catalyst includes at least one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, and W.
[0046] Adding transition metal acetates, transition metal oxalates, and transition metal citrates as catalysts to lithium supplements is mainly to utilize the electrochemical activity of these organic transition metal salts to promote the decomposition process of lithium oxalate. These metal catalysts can accelerate the release rate of lithium ions and effectively reduce the decomposition voltage of lithium oxalate during battery charging, thereby allowing the battery to complete the lithium supplement process at a lower voltage and improve the battery's energy density and cycle life.
[0047] Preferably, the catalyst comprises acetate, oxalate and citrate containing at least one of Ti, Mn, Fe, Co, Ni, Cu, Zn, Mo and W.
[0048] In some embodiments of the present application, the mass ratio of lithium oxalate, carbon material and catalyst is (60-98):(1-39):(1-39).
[0049] Lithium oxalate is the main active material, with a high proportion of lithium oxalate, ensuring sufficient lithium ion supply to support the high energy demand of the battery. Carbon material is used as a conductive framework, with a lower proportion in the overall mixture, but sufficient to provide the necessary electronic conductivity and structural support. The content of the catalyst is also within a relatively low range, in order to ensure the decomposition efficiency of lithium oxalate while maximizing the content of lithium oxalate, thereby improving the release rate of lithium ions and the overall performance of the battery.
[0050] By adjusting the ratio of the three materials, the best performance balance can be found to achieve the highest electrochemical efficiency and the best battery performance. This range of adjustment allows the lithium supplement to be optimized according to different application requirements, such as increasing the proportion of lithium oxalate in applications that require higher energy density, or increasing the proportion of carbon materials when higher conductivity is required. By fine-tuning the ratio of ingredients, costs can be controlled while maintaining performance, making the production process more economical and efficient.
[0051] It should be noted that the mass of the catalyst is the mass after removing the crystal water.
[0052] In some embodiments of the present application, the morphology of the lithium supplement includes at least one of secondary spherical particles composed of primary particles and secondary block particles composed of primary particles.
[0053] The lithium supplement in the form of secondary spherical or block particles is formed by the aggregation of multiple primary particles into larger spherical or block particles. This structure is beneficial to improving the uniformity and reaction area of the material while ensuring the overall stability of the material, preventing lithium oxalate from losing electrical contact with the carbon material and the catalyst during the slurry stage, thereby ensuring that its electrochemical activity in the battery system can be fully exerted.
[0054] In some embodiments of the present application, the particle size D50-1 of the primary particles is 20nm-200nm; and / or the particle size D50-2 of the secondary spherical particles is 3μm-30μm; and / or the particle size D50-3 of the secondary block particles is 3μm-30μm.
[0055] As the basic building block, primary particles within the particle size range of 20nm-200nm are conducive to maintaining high surface activity and faster reaction kinetics, accelerating the transmission of lithium ions, and promoting the decomposition of lithium oxalate at a lower voltage. By aggregating fine primary particles into larger spherical particles or block particles, the structural stability and ease of handling of the particles can be improved, preventing lithium oxalate from breaking during the homogenization stage while maintaining good electrochemical properties. This particle size range helps the lithium oxalate supplement to perform its lithium supplement performance in the battery system.
[0056] The lithium supplement provided by the present invention is a secondary particle composed of primary particles, and the primary particles of lithium oxalate and the catalyst are filled in a conductive network constructed by a carbon material to form secondary particles, and the secondary particles include at least one of secondary spherical particles and secondary block particles. Since the carbon material does not undergo a morphological change before and after spray drying, the particle size remains unchanged; the catalyst is precipitated in situ, and its particle size cannot be observed; therefore, the particle size of the primary particles of lithium oxalate is mainly observed, and the particle size of the primary particles in the present invention is the particle size of the primary particles of lithium oxalate.
[0057] In some embodiments of the present application, the carbon material includes at least one of a zero-dimensional material, a one-dimensional material, or a two-dimensional material.
[0058] Zero-dimensional materials refer to nanoparticles or quantum dots. These materials are extremely small in all three dimensions, so they have a high specific surface area, which significantly improves electrochemical activity and catalytic performance. One-dimensional materials such as carbon nanotubes or carbon nanofibers are known for their excellent electrical conductivity and mechanical properties. They are very suitable as electrode materials and can effectively improve the conductivity and structural strength of batteries. Two-dimensional materials such as graphene have a unique layered structure, provide extremely high surface area and excellent electronic and thermal conductivity, and are suitable for high-performance batteries and supercapacitors.
[0059] The use of these carbon materials of different dimensions can customize battery performance according to specific application requirements, such as enhancing the electrochemical reaction rate through zero-dimensional materials, or improving the structural stability and conductivity of the electrode through one-dimensional materials. Two-dimensional materials such as graphene can achieve high energy density and fast charge transfer in batteries, which plays an important role in improving the charging and discharging speed and power output of batteries. Combining these carbon materials of different dimensions can achieve complementary material properties, such as maintaining or enhancing the mechanical properties and thermal stability of the material while enhancing the electrochemical performance.
[0060] Preferably, the carbon material is one or more of the conductive carbon materials of various dimensions, wherein the zero-dimensional ones are mainly various conductive carbon granular materials, including at least one of KB, Super P, KS6, fullerene, etc.; the one-dimensional ones are mainly various fibrous or tubular conductive carbon materials, including at least one of CNT, carbon nanowire, carbon fiber, etc.; the two-dimensional ones are mainly various flaky conductive carbon materials, such as at least one of graphene (GO, rGO), graphyne, MXenes, etc. Further preferably, the carbon material includes KB, CNT, graphene.
[0061] An embodiment of the present invention also provides a method for preparing a lithium supplement, which is used to prepare the lithium supplement as described above, and the preparation method comprises the following steps: S1, dissolving, stirring, and ultrasonically dispersing lithium oxalate, a carbon material, and a catalyst in sequence to obtain a slurry; S2, spray-drying and granulating the slurry in sequence to obtain a powder material; S3, drying the powder material to obtain a lithium supplement.
[0062] In the pretreatment mixing step, lithium oxalate, carbon material, and catalyst are dissolved, stirred, and ultrasonically dispersed in sequence, which helps ensure that all ingredients are evenly mixed to form a stable slurry. The prepared slurry is then quickly dried by spray drying technology and then granulated. This process not only removes the solvent in the slurry, but also converts it into a more uniform and suitable powder form through granulation. Finally, the powder material is finally dried to remove possible residual moisture and ensure that the final lithium supplement has good storage and use stability.
[0063] The lithium supplement prepared by this method can effectively replenish the loss of lithium in the battery and improve the battery's charge and discharge capacity and cycle life. Through the use of stable carbon materials and catalysts, the risks of battery operation, such as overheating and thermal runaway, can be reduced. The entire preparation process is controllable and suitable for large-scale production, which helps to reduce costs and ensure product consistency and quality.
[0064] Furthermore, by dissolving lithium oxalate and the catalyst in water and then spray drying, the two substances can be uniformly precipitated together in the form of nanoparticles and composited with the carbon material. This method not only simplifies the production process, but also ensures the high uniformity and high performance of the composite material. During the charging process of the battery, this structure can maximize the lithium replenishment effect of lithium oxalate and improve the overall performance and life of the battery. Among them, the spray drying form includes rotary dispersion disk spray drying and jet two-fluid spray drying.
[0065] In some embodiments of the present application, the dissolution in step S1 specifically includes: dissolving lithium oxalate and a catalyst in water to obtain a mixed solution, and then adding the carbon material to the mixed solution; wherein the carbon material is in the form of at least one of a powder or a slurry.
[0066] In step S1, lithium oxalate and the catalyst are first dissolved in water to form a mixed solution. This operation ensures that the lithium oxalate and the catalyst can be fully dissolved, creating conditions for the subsequent mixing and reaction. Next, the carbon material is added to the mixed solution in the form of powder or slurry. The addition of carbon material not only enhances the conductivity of the solution, but also provides better structural stability and battery performance. To ensure the dispersibility of the carbon material, the carbon material is used in the form of a dry powder material and a slurry. The slurry contains a dispersant such as CMC to improve the dispersibility of the carbon material.
[0067] By pre-dissolving lithium oxalate and the catalyst in water before adding the carbon material, it is more effective to ensure that all ingredients are evenly mixed, which is critical to the quality and consistency of the final product. This dissolution and mixing method can speed up the production process, simplify the operation steps, and help improve the overall preparation efficiency.
[0068] In some embodiments of the present application, the concentration of lithium oxalate in the slurry is less than the saturation concentration of lithium oxalate.
[0069] The concentration of lithium oxalate used is set to be lower than its saturation concentration in the corresponding solvent. This means that the lithium oxalate is completely dissolved in the slurry, and there are no undissolved solid particles, thus ensuring the uniformity and stability of the solution. Keeping the concentration of lithium oxalate below the saturation point can prevent crystallization or precipitation during the preparation process or long-term storage, thereby improving the stability of the slurry; it can also ensure a more uniform distribution of materials, which is particularly important in the electrode coating process and helps to improve the consistency of battery assembly and the performance of the final battery; solutions that do not reach the saturation concentration have good fluidity and processability, and are easy to adjust and apply in subsequent processing steps, providing greater flexibility for battery design and manufacturing.
[0070] The concentration of lithium oxalate is less than the saturation concentration of lithium oxalate, preferably, the concentration of lithium oxalate is 2%-5.5%. The catalyst is added in a ratio to lithium oxalate.
[0071] An embodiment of the present invention further provides a lithium ion battery, which includes the lithium supplement as described above.
[0072] Example 1
[0073] An embodiment of the present invention provides a method for preparing a lithium supplement, comprising the following steps:
[0074] S10, add 20g manganese acetate and 160g lithium oxalate to an appropriate amount of deionized water, stir until manganese acetate and lithium oxalate are completely dissolved. Then add 10g KB, stir and ultrasonicate for 2h each to form a uniform suspension slurry of KB, manganese acetate and lithium oxalate;
[0075] S20, spray drying the prepared slurry using a spray dryer, with an air inlet temperature of 240° C. and a centrifugal dispersion disk as the spraying form. The spray-dried powder is collected and vacuum-dried to obtain the final lithium oxalate lithium supplement.
[0076] The prepared lithium oxalate lithium supplement was subjected to a button half-cell constant current and constant voltage charging test, with a test current of 0.1C (nominal capacity 525mAh / g), a cut-off voltage of 4.35V, and a constant voltage cut-off current of 0.05C. The obtained charge specific capacity is the decomposition capacity of lithium oxalate, and the obtained average charge voltage is the average decomposition voltage of lithium oxalate.
[0077] The preparation methods of the lithium oxalate lithium supplements of Examples 2-37 and Comparative Examples 1-9 can refer to Example 1, and the specific parameter selection and measurement results can be seen in Table 1.
[0078] Table 1 Parameter selection and measurement results of Examples 1-37 and Comparative Examples 1-9
[0079]
[0080]
[0081]
[0082]
[0083] It can be seen from Table 1 that the lithium oxalate supplement prepared in Examples 1-37 has a higher decomposition capacity and a lower decomposition voltage than Comparative Examples 1-9. Among them, the lithium oxalate supplement provided in the examples has an average decomposition voltage of less than 4.25V and a decomposition capacity of 300mAh / g-500mAh / g.
[0084] According to the comparison of Examples 1-3, Examples 10-17, Comparative Example 1, Comparative Examples 4-9, and the comparison of Examples 8-9 and Comparative Examples 2-3, it can be seen that when the catalyst is a transition metal acetate, a transition metal oxalate or a transition metal citrate, and the catalyst contains at least one of the elements Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, and W, the decomposition capacity of the lithium oxalate lithium supplement of the embodiment is significantly higher than that of the comparative example, and the average decomposition voltage of the lithium oxalate lithium supplement of the embodiment is significantly lower than that of the comparative example, which indicates that the catalyst selected in this embodiment can significantly reduce the decomposition voltage of the lithium oxalate lithium supplement and promote the use of the capacity of the lithium oxalate lithium supplement. Figure 1 is the SEM image of Example 1; Figure 2 is the SEM image of Example 4; Figure 3 This is the SEM image of Example 1.
[0085] The lithium supplement provided by the present invention is a secondary particle composed of primary particles. The primary particles of lithium oxalate and the catalyst are filled in the conductive network constructed by the carbon material to form the secondary particles. The secondary particles include at least one of secondary spherical particles and secondary block particles. It can be foreseen that the carbon material does not change its morphology before and after spray drying, so the particle size does not change; the catalyst is precipitated in situ, and its particle size cannot be observed; therefore, the particle size of the primary particles of lithium oxalate is mainly observed, such as Figure 3 As shown in Table 2, the particle size of the primary particles in the present invention is the particle size of the primary particles of lithium oxalate. The particle size of the primary particles and the particle size of the secondary particles are directly observed by SEM. As shown in Table 2, the secondary particle size data of the lithium supplement in Example 1 and Example 4 are provided.
[0086] Table 2 Particle size data of lithium supplement provided in Example 1 and Example 4
[0087]
[0088] According to the professional knowledge in this field, the spray drying equipment can obtain secondary particle sizes of different sizes in a wide range by adjusting the rotation speed of the centrifugal dispersion disk and the injection pressure of the two fluids. The spray dryer used in the present invention is the HF-10L spray dryer of Shanghai Hefan Instrument Co., Ltd., the atomizer frequency is 380Hz when the centrifugal dispersion disk sprays, and the injection pressure is 0.3MPa when the two fluids spray.
[0089] The embodiments of the present invention further provide a method for preparing a sodium supplement. The preparation methods of the sodium oxalate sodium supplements of Examples 38-40 and Comparative Example 10 can refer to Example 1. The specific parameter selection and measurement results can be seen in Table 3.
[0090] The prepared sodium oxalate supplement was subjected to a button half-cell constant current and constant voltage charging test, with a test current of 0.1C (nominal capacity 382mAh / g), a cut-off voltage of 4.20V, and a constant voltage cut-off current of 0.05C. The obtained charge specific capacity is the decomposition capacity of sodium oxalate, and the obtained average charge voltage is the average decomposition voltage of sodium oxalate.
[0091] Table 3 Parameter selection and measurement results of Examples 38-40 and Comparative Example 10
[0092]
[0093] It can be seen from Table 3 that the sodium oxalate capacity compensators prepared in Examples 38-40 have higher decomposition capacity and lower decomposition voltage compared to Comparative Example 10. Among them, the lithium oxalate capacity compensator provided in the examples has an average decomposition voltage of less than 4.10 V and a decomposition capacity of 320 mAh / g-400 mAh / g.
[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium supplement, characterized in that: The lithium supplement comprises lithium oxalate, a carbon material and a catalyst, wherein the lithium oxalate and the catalyst are filled in a conductive network constructed by the carbon material; Wherein, the catalyst comprises at least one of transition metal acetate, transition metal oxalate, transition metal citrate and hydrates thereof; The transition metal in the catalyst includes at least one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, and W.
2. The lithium supplement according to claim 1, characterized in that: The mass ratio of the lithium oxalate, the carbon material and the catalyst is (60-98): (1-39): (1-39).
3. The lithium supplement according to claim 1, characterized in that: The morphology of the lithium supplement agent includes at least one of secondary spherical particles composed of primary particles and secondary block particles composed of primary particles.
4. The lithium supplement according to claim 3, characterized in that: The particle size D50-1 of the primary particles is 20nm-200nm; and / or The particle size D50-2 of the secondary spherical particles is 3 μm-30 μm; and / or The particle size D50-3 of the secondary block particles is 3 μm-30 μm.
5. The lithium supplement according to claim 1, characterized in that: The carbon material includes at least one of a zero-dimensional material, a one-dimensional material or a two-dimensional material.
6. A method for preparing a lithium supplement, characterized in that: For preparing the lithium supplement according to any one of claims 1 to 5, the preparation method comprises the following steps: S1, dissolving, stirring, and ultrasonically dispersing the lithium oxalate, the carbon material, and the catalyst in sequence to obtain a slurry; S2, spray drying and granulating the slurry in sequence to obtain a powder material; S3, drying the powder material to obtain the lithium supplement agent.
7. The preparation method according to claim 6, characterized in that: The dissolving in step S1 specifically includes: dissolving the lithium oxalate and the catalyst in water to obtain a mixed solution, and then adding the carbon material to the mixed solution; The carbon material is in the form of at least one of powder or slurry.
8. The preparation method according to claim 6, characterized in that: The concentration of the lithium oxalate in the slurry is less than the saturation concentration of the lithium oxalate.
9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium supplement according to any one of claims 1 to 5.
Citation Information
Patent Citations
Modified lithium oxalate lithium supplement agent and preparation method and application thereof
CN116666603A
Lithium oxalate lithium supplement agent and preparation method and application thereof
CN118231661A
Composite lithium supplement agent as well as preparation method and application thereof
CN118507701A